Geochemical distribution and occurrence of rare earth elements in stream sediments of Tamiang, Aceh, Indonesia - Nugraha, Gartika Setiya; Edward, Hamzah Nailan; Taufiq, Muhammad; Fakhrurrazi, Fakhrurrazi (Geologos, 2025)
This study investigates the geochemical distribution of rare earth elements (REEs) in stream sediments from the Aceh Tamiang Regency, Aceh Province, Indonesia, an area characterized by a complex geological framework and potential lanthanide-bearing source rocks. Rare earth elements such as lanthanum (La), scandium (Sc), and yttrium (Y) are essential to modern high-technology and clean-energy applications, yet baseline data from this region remain limited. A total of forty stream sediment samples were collected from the Simpang Kanan, Simpang Kiri, Tamiang, and Tenggulun rivers to determine the spatial distribution and concentration levels of La, Sc, and Y. All three elements were detected in the riverbed sediments in the study area, with La showing higher concentrations (average 11 ppm) compared to Sc (2 ppm) and Y (3 ppm). Higher values are observed in upstream sediments underlain by igneous and metamorphic rocks, while lower values occur in downstream sedimentary zones. This distribution pattern indicates that the enrichment of REEs is primarily derived from the weathering of upstream source rocks. Additionally, the presence of active tectonic structures in the region may have contributed to the mobilization and accumulation of these elements. This study establishes a baseline of REE distribution in stream sediments of Tamiang and provides valuable data that may support broader regional geochemical investigations.